Strategi Pondok Pesantren dalam Membina Kader Da’i di Kabupaten Padang Lawas Sumatera Utara - Asrul Harahap (UIN Antasari Banjarmasin, 2022)
The purpose of this research is to find out: 1) the strategy of Islamic boarding schools in building the substantive competence of students in preaching, 2) the strategy of Islamic boarding schools in building the methodological competence of students in preaching. To find out how the results of this research were carried out with descriptive qualitative research with data collection techniques through interviews, observation and documentation. From the results of this study, it can be concluded that the strategy of Islamic boarding schools in building the substantive competence of students in preaching includes coaching that leads to strengthening Islamic values, so that these Islamic values will be seen from their breadth of knowledge and morals. While the development of the methodological competence of students in preaching includes building the abilities that exist in students in preaching, so that they are able to make good da'wah plans, as well as being able to carry out these plans and master the capability of da'wah.